Про початковий етап будівництва в античному Херсонесі - Золотарьов, М.І. (Археологія, 1990)
У публікації вводяться до наукового обігу результати досліджень у Північно-Східному районі Херсонеського городища, в результаті яких були виявлені найдавніші житлові споруди поліса. В процессе исследования третьего квартала Северо-Восточного района Херсонеса в 1983 г. были открыты углубленные в скалу сооружения. Это два вырубленных в скале жилища круглой и овальной формы с глинобитными полами, очагом и тамбуром. Есть основания полагать, что наземные части построек были сложены из сырцового кирпича. На полу в сооружениях найдены остродонные античные амфоры с керамическими клеймами, датирующиеся в пределах конца V — первой четверти IV вв. до н. э. К этому же времени относится и многочисленная аттическая чернолаковая керамика, лепная и ионийская посуда.
Скальные сооружения, открытые в Херсокесе, являются древнейшими жилыми постройками города, подобными полуземлянкам Ольвии, Березани и других памятников Северо-Западного Причерноморья. Они возникают с основанием дорийского Херсонеса и существуют в первой четверти IV в. до н. э. Около середины IV века до н. э. на месте углубленных в скалу жилищ возводятся наземные каменные постройки. Structures deepened in the rock were discovered in 1983 when studying the third quarter of the Northern-Eastern region of Khersones. Those were two dwellings of the round and oval shape hollowed out in the rock. They had wattle and daub floor, a hearth and a tambour. There are grounds to suppose that the ground parts of structures were composed of the raw brick. Acute-bottom antique amphoras with ceramic brands dating them back to the end of the 5th and first quarter of the 4th cent B.C. were found on the floor of the dwellings. A variety of attic black-varnish pottery, modelled and Jonian dishes are dated back to the same period.
Rock structures discovered in Khersones are the most ancient dwellings of the town similar to the semiearth-houses of Olvia, Berezan and other monuments of the North-Western Black Sea area. They appeared with foundation of the Dorian Khersones and existed in the first quarter of the 4th century B.C. In the middle of the 4th century B.C. ground stone structures appeared in the plates of the dwellings hollowed out in rock.